DETEKSI VIRUS HEPATITIS E (HEV) DAN HANTAVIRUS PADA INANG RESERVOIR (TIKUS) DI KABUPATEN KLATEN DAN KENDAL, PROVINSI JAWA TENGAH - Arief Mulyono; Tika Fiona Sari; Ristiyanto Ristiyanto; Bernadus Yuliadi; Edi Royandi; Ayu Pradipta Pratiwi (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
Rats are animal reservoirs and harbours of several zoonotic pathogens diseases in humans. At least, there are 68 viruses of zoonotic agents that can be transmitted by rats. Two common types of viruses attackinghumans are Hepatitis E virus (HEV) and Hantavirus. Early detection of those viruses is fundamentally required in order to prevent disease transmissions to humans. The aim of the study was to detect and count the percentage of rats infected by HEV and Hantavirus in Kendal and Klaten Districts, Central Java Province. The research design used in this study was descriptive design with cross-sectional approach. The target population was rats distributed in Klaten and Kendal Districts. In addition, the research subject was trapped rats. Detection of Hantavirus was carried out using ELISA method and detection of HEV was conducted using nested reverse transcription PCR (nested RT-PCR). A total of 73 rats was successfully captured consisting of 2 genus and 4 species e.g. Rattus novergicus, R. tanezumi, R. tiomanicus and Bandicota indica. The trapped rats infected by HEV were 3.7% and 41.3% for Klaten and Kendal, respectively. However, the seropositive of Hantavirus was only found in Kendal District (20.5%). Rat control is necessary to prevent transmission of HEV and Hantavirus.